Coronary vasculature patterning requires a novel endothelial ErbB2 holoreceptor - Haig Aghajanian (Nature Portfolio, 2016)
Semaphorin ligands and cognate receptors are important in patterning the vasculature. Here, Aghajanian et al.report an unexpected role for ErbB2 in endothelial cells where it partners with Nrp1 to form a novel semaphoring holoreceptor required for embryonic vascular patterning.